Analisis Fishbone Diagram Pada Kerusakan Turbin Blade dan Dampaknya Pada Kinerja Turbocharger Main Engine di Kapal Km Sirimau - Abhyasa, Ardian; Robbi, Shofa Dai; Gupron, Akhmad Kasan; Prawoto, Agus; Syahputra, Rama (Universitas Pahlawan Tuanku Tambusai, 2025)
The turbocharger is a critical component in a ship's main engine system, enhancing combustion efficiency and engine performance by accelerating airflow into the cylinder combustion chamber. One of its key components is the turbine blade, which converts exhaust gas energy into mechanical energy to drive the compressor.This study aims to analyze damage to the turbine blade caused by exhaust valve rupture, where broken valve fragments enter the turbine side, negatively affecting turbocharger performance. The research employs a descriptive analysis method using fishbone analysis, with data collected from observations, logbooks, journals, manuals, documentation, and interviews.The findings indicate that the primary cause of turbine blade damage is foreign object ingestion (FOI), specifically fragments from a fractured exhaust valve in the main engine’s cylinder head. This fracture led to blade failure, significantly reducing the turbocharger’s efficiency. To maintain optimal main engine performance, strict adherence to the onboard manual book is strongly recommended.